2005
DOI: 10.1098/rstb.2005.1720
|View full text |Cite|
|
Sign up to set email alerts
|

Land plants and DNA barcodes: short-term and long-term goals

Abstract: Land plants have had the reputation of being problematic for DNA barcoding for two general reasons: (i) the standard DNA regions used in algae, animals and fungi have exceedingly low levels of variability and (ii) the typically used land plant plastid phylogenetic markers (e.g. rbcL, trnL-F, etc.) appear to have too little variation. However, no one has assessed how well current phylogenetic resources might work in the context of identification (versus phylogeny reconstruction). In this paper, we make such an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
464
2
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(498 citation statements)
references
References 18 publications
12
464
2
8
Order By: Relevance
“…Early work on marine algae (16) revealed that CO1-based systems are promising for this group. In contrast, this gene will be less effective for land plants because of their slower mitochondrial evolution, and efforts are underway to identify alternate gene regions that will deliver species-level resolution (17)(18)(19). The potential effectiveness of CO1 in species identification of fungi has not yet been evaluated, and the present study represents a first step to address this gap.…”
mentioning
confidence: 97%
“…Early work on marine algae (16) revealed that CO1-based systems are promising for this group. In contrast, this gene will be less effective for land plants because of their slower mitochondrial evolution, and efforts are underway to identify alternate gene regions that will deliver species-level resolution (17)(18)(19). The potential effectiveness of CO1 in species identification of fungi has not yet been evaluated, and the present study represents a first step to address this gap.…”
mentioning
confidence: 97%
“…However, the universality of barcode markers is hampered due to morphological/geographical variation and reticulate evolution in plant species (Roy et al, 2010). The ongoing research on plant barcoding suggests that the development of universal DNA barcoding markers for land plants is challenging; even the choice of the correct loci has been debated (Chase et al, 2005;Kress et al, 2005;Fazekas et al, 2008;de Groot et al, 2011). Arguments about the selected core loci for plant barcoding are related to the lack of discriminatory power and/or primer universality (Roy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is admittedly uncertain how well cox1-5 0 will function for species discrimination in the other kingdoms of life because the mode of inheritance, rate of divergence, as well as many of the other attributes discussed above for this marker, are poorly known outside of the animals and land plants. For the latter, it was established that mitochondrial genes are generally more slowly evolving than in animals (Barkman et al 2000), but that the more rapidly evolving plastid genome may provide sequences that would be adequate candidates for genetic barcoding (Chase et al 2005). As for the many unicellular and multicellular protists, little is known and only through exploratory research will the utility of cox1-5 0 as a genetic marker be established for the various lineages.…”
Section: Introductionmentioning
confidence: 99%